Given:

\(x+y=5 \rightarrow\)(1)

\(2x-3y=4 \rightarrow\)(2)

solution by elimination method:

\([2 \cdot equation(1)]-[equation(2)]\)

\(\Rightarrow 2(x+y)-(2x-3y)=2(5)-4\)

\(\Rightarrow 5y=6\)

\(\Rightarrow y=6/5\)

\(\Rightarrow y=1.2\)

now substituting \(y=1.2\) in equation(1),we ge

\(x+1.2=5 \Rightarrow x=3.8\)

\(x=3.8\) and \(y=1.2\)

solution by substitution method

From equation \(\rightarrow\)(1), we have

\(x+y=5 \Rightarrow y=5-x\)

now substituting \(y=5-x\) in equation(2), we get

\(2x-3(5-x)=4 \Rightarrow 2x-15+3x=4 \Rightarrow 5x=19 \Rightarrow x=3.8\)

now substituting \(x=3.8+\) in equation (1),we get

\(3.8+y=5 \Rightarrow y=1.2\)

\(x=3.8\) and \(y=1.2\)